(untitled) (GENDER EQUALITY: International Journal of Child and Gender Studies, 2017)
This paper highlights the opinions among the academic community UIN Ar-Raniry aboutthe protection of children which recommends need for facilities for children in the working environment. This article is inspired from the increasing number of violence against children nowadaye.Provision 1 paragraph 2 of Law No. 23 of 2002 on Child Protection that referred to child protection is all activities to ensure and protect children and their rights in order to live, grow, develop, and participate optimally in accordance with the dignity of the human, as well as protection from violence and discrimination. This research is a quantitative research using a survey method. This method is applied to gather data to answer the problem.The questionnaire are given to the academic community of UIN Ar-Raniry on child protection issues obtained thatcommunity, have a high response to the protection of children who desperately wanted facilities for children in the work environment.